CORRELATION BETWEEN TECHNOLOGICAL READINESS AND BUSINESS SOPHISTICATION IN GLOBAL COMPETITIVENESS - Gama Harta Nugraha Nur Rahayu (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2020)
In today’s global economy, the competitiveness of a country has important role to bring the country into prosperity and a respectable position among others. That is why during the past decade, scholars, policy makers and even business leaders throughout the world put a very serious attentions to the issue. Since 1979, the World Economic Forum has published the Global Competitiveness Report which encompasses Global Competitiveness Index (GCI) in order to measure national competitiveness in different countries throughout the world. Using the two sets of variables of “Technological Readiness” and “Business Sophistication” as the two basic pillars of national competitiveness, this study is aimed at investigating the interaction between the two pillars in order to help countries which are in transition from stage II to stage III of development by providing meaningful information for their national competitiveness improvement. This study used descriptive-correlation methodology. According to the GCI 2010 report which covered a statistical population of 139 countries, the secondary analysis using Canonical Correlation Analysis was done. The result shows that there is a significant and positive relationship between the set of variables of “Technological Readiness” and “Business Sophistication”.